Isotope shift of the 1s2 p 3P0-1s2s 1S0 level splitting in heavy He-like ions: implications for atomic parity-nonconservation studies - Ferro, Fabrizio; Artemyev, Anton; Stöhlker, Thomas; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2010)
Heavy He-like ions are considered to be promising candidates for atomic parity-nonconservation (PNC) studies, thanks to their relatively simple atomic structure and the significant mixing between the almost degenerate (for the atomic numbers Z~64 and Z~91) opposite-parity levels 1s2s1S0 and 1s2p3P0. A number of experiments exploiting this level mixing have been proposed, and their implementation requires a precise knowledge of the 23P0-21S0 energy splitting for different nuclear charges and isotopes. In this paper we performed a theoretical analysis of the level splitting, employing the relativistic many-body perturbation theory and including QED corrections for all isotopes in the intervals 54⩽Z⩽71 and 86⩽Z⩽93. Possible candidates for future experimental PNC studies are discussed.
Im Titel ist die Ziffer 3 bei 3P0 und die Ziffer 1 bei 1S0 jeweils hochgestellt, die Ziffer 0 überall tiefgestellt
Gesehen am 18.12.2023